The Immunomodulatory Effects of Mesenchymal Stem Cells on Regulatory B Cells - Liu, Jialing; Liu, Qiuli; Chen, Xiaoyong (Frontiers in Immunology, 2020)
The therapeutic potential of mesenchymal stem cells (MSCs) has been investigated in many preclinical and clinical studies. This potential is dominantly based on the immunosuppressive properties of MSCs. Although the therapeutic profiles of MSC transplantation are still not fully characterized, accumulating evidence has revealed that B cells change after MSC infusion, in particular inducing regulatory B cells (Bregs). The immunosuppressive effects of Bregs have been demonstrated, and these cells are being evaluated as new targets for the treatment of inflammatory diseases. MSCs are capable of educating B cells and inducing regulatory B cell production via cell-to-cell contact, soluble cytokines and extracellular vesicles (EVs). These cells thus have the potential to complement each other's immunomodulatory functions, and a combined approach may enable synergistic effects for the treatment of immunological diseases. However, compared with investigations regarding other immune cells, investigations into how MSCs specifically regulate Bregs have been superficial and insufficient. In this review, we discuss the current findings related to the immunomodulatory effects of MSCs on regulatory B cells and provide optimal strategies for applications in immune-related disease treatments.